Acquired lecithin:cholesterol acyltransferase deficiency as a major factor in lowering plasma HDL levels in chronic kidney disease. (1st August 2014) - Calabresi, L.; Simonelli, S.; Conca, P.; Busnach, G.; Cabibbe, M.; Gesualdo, L.; Gigante, M.; Penco, S.; Veglia, F.; Franceschini, G.
Abstract Objectives It has been suggested that a low plasma high‐density lipoprotein cholesterol (HDL‐C) level contributes to the high cardiovascular disease risk of patients with chronic kidney disease (CKD), especially those undergoing haemodialysis (HD). The present study was conducted to gain further understanding of the mechanism(s) responsible for the low HDL‐C levels in patients with CKD and to separate the impact of HD from that of the underlying CKD. Methods Plasma lipids and lipoproteins, HDL subclasses and various cholesterol esterification parameters were measured in a total of 248 patients with CKD, 198 of whom were undergoing HD treatment and 40 healthy subjects. Results Chronic kidney disease was found to be associated with highly significant reductions in plasma HDL‐C, unesterified cholesterol, apolipoprotein (apo)A‐I, apoA‐II and LpA‐I:A‐II levels in both CKD cohorts (with and without HD treatment). The cholesterol esterification process was markedly impaired, as indicated by reductions in plasma lecithin:cholesterol acyltransferase (LCAT) concentration and activity and cholesterol esterification rate, and by an increase in the plasma preβ‐HDL content. HD treatment was associated with a further lowering of HDL levels and impaired plasma cholesterol esterification. The plasma HDL‐C level was highly significantly correlated with LCAT concentration (R = 0.438, P < 0.001), LCAT activity (R = 0.243, P < 0.001) and cholesterol esterification rate (R = 0.149, P = 0.031). Highly significant correlations were also found between plasma LCAT concentration and levels of apoA‐I (R = 0.432, P < 0.001), apoA‐II (R = 0.275, P < 0.001), LpA‐I (R = 0.326, P < 0.001) and LpA‐I:A‐II (R = 0.346, P < 0.001). Conclusion Acquired LCAT deficiency is a major cause of low plasma HDL levels in patients with CKD, thus LCAT is an attractive target for therapeutic intervention to reverse dyslipidaemia, and possibly lower the cardiovascular disease risk in these patients.